1999
DOI: 10.1111/j.1532-5415.1999.tb05199.x
|View full text |Cite
|
Sign up to set email alerts
|

Falls Relate to Vitamin D and Parathyroid Hormone in an Australian Nursing Home and Hostel

Abstract: In ambulant nursing home and hostel residents, residents who fall have lower serum 25-hydroxyvitamin D and higher serum parathyroid hormone levels than other residents. The association between falling and serum PTH persists after adjustment for other variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
137
0
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(154 citation statements)
references
References 57 publications
5
137
0
10
Order By: Relevance
“…The low D-hormone serum levels observed with a creatinine clearance of <65 ml/min may also be one reason for the increased osteopenia and osteoporosis observed with low creatinine clearance by other authors [15,16]. Our result enhances the theory suggested by other studies [4,5,6,7,17,18,19,20,21,22] that D-hormone is an independent risk factor for falls [1,2,5,23], and that D-hormone is directly involved in the causal pathogenic pathway of decreased muscle strength related falls [9,23,24]. It has been recently confirmed in VDR gene deleted mice that the absence of VDR causes muscle abnormality independently of secondary metabolic changes, e.g.…”
Section: Discussionsupporting
confidence: 79%
“…The low D-hormone serum levels observed with a creatinine clearance of <65 ml/min may also be one reason for the increased osteopenia and osteoporosis observed with low creatinine clearance by other authors [15,16]. Our result enhances the theory suggested by other studies [4,5,6,7,17,18,19,20,21,22] that D-hormone is an independent risk factor for falls [1,2,5,23], and that D-hormone is directly involved in the causal pathogenic pathway of decreased muscle strength related falls [9,23,24]. It has been recently confirmed in VDR gene deleted mice that the absence of VDR causes muscle abnormality independently of secondary metabolic changes, e.g.…”
Section: Discussionsupporting
confidence: 79%
“…Both factors-increasing IL-6 and decreasing IGF-I-are synergistic risk factors for functional disability [42]. The results from these studies [9,10,11,28,29,30,40,41,42] suggest that 1.25(OH) 2 D 3 is an independent risk factor for decreased muscle strength [12,13], reduced functional mobility [14], and for falls [8,16,17,43], suggesting a direct involvement of 1.25(OH) 2 D 3 in the causal pathogenic pathway of decreased muscle strength-related falls [39].…”
Section: Discussionmentioning
confidence: 98%
“…Thus it is difficult to distinguish any separate effects on muscle function. Stein and colleagues (39) have suggested that the muscle effect of 25(OH)D insufficiency could be due to iPTH and not to a direct action of vitamin D on muscle. This relationship between serum iPTH concentrations and muscle has been known for a long time in patients with primary hyperparathyroidism, whose clinical features include muscle weakness (40) that was reversed after parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%